The Role of Social Media in the Formation of Political Image: An Analysis of the Facebook Profiles of Boyko Borisov, Slavi Trifonov and Kiril Petkov in 2021. - Papazova, Plamena (Media and Language, 2023)
Nowadays, social media plays an increasingly important role in public and political life and has become an important channel of communication between politicians and citizens. In this context, this article will explore the role of social media in building political image, focusing on the profiles of leading politicians in Bulgaria in 2021. The article will consider the winners of the three rounds of the 2021 parliamentary elections and analyze the Facebook profiles of the respective party leaders. For the analysis of their activity on Facebook, the number of posts, their topic, their volume, as well as whether they include a photo, video, or link to an external post and whether they use a hashtag will be considered. Reactions, comments, and shares of the posts were also tracked to account for audience engagement with the posts. The research can provide useful information about the use of social media in political communication.
Keywords: political image; social media; Facebook; election campaigns